Lauriomyces, a New Lineage in the Leotiomycetes with Three New Species - Somrithipol, Sayanh; Jones, E. B.Gareth; Bahkali, A. H.; Suetrong, Satinee; Sommai, Sujinda; Chamoi, Chalida; Johnston, Peter R.; Cooper, Jerry A.; Rungjindamai, Nattawut (My University, 2017)
Lauriomyces is an anamorphic genus comprising nine species, found growing on terrestrial leaf litter and wood in tropical habitats. The genus is characterized by solitary or synnematous, pigmented conidiophores bearing acropetal chains of unicellular, hyaline conidia.Amultigene (SSU, LSU & 5.8S) analysis of Lauriomyces strains reveal three cryptic new species, which are described, illustrated, and published here: L. acerosus, L. basitruncatus, and L. glumateus spp. nov. Lauriomyces glumateus is characterized by narrowly oval conidia while conidia of L. acerosus are cylindrical with acute ends and those of L. basitruncatus are cylindrical with truncate base. The nine Lauriomyces species sampled form a monophyletic clade in the Leotiomycetes, with high molecular support and all with a morphology typical for the genus. The new combination Dematioscypha catenata is made for Haplographium catenatum in compliance with the one name protocol.
Keywords: Anamorphic fungi; Leotiomycetes; Saprobic microfungi; Taxonomy